2016
DOI: 10.3390/met6110284
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Wear Properties of Electron Beam Melted Ti-6Al-4V Parts: A Comparison Study against As-Cast Form

Abstract: Ti-6Al-4V (Ti64) parts of varying thicknesses were additively manufactured (AM) by the powder-bed-based electron beam melting (EBM) technique. Microstructure and wear properties of these EBM-built Ti-6Al-4V parts have been investigated in comparison with conventionally cast Ti64 samples. Sliding wear tests were conducted using a ball-on-disc micro-tribometer under ambient conditions. Experimental results reveal that EBM-built Ti64 samples exhibited higher microhardness and an overall larger coefficient of fric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 30 publications
(46 reference statements)
1
23
0
Order By: Relevance
“…Even though, the authors reported that SLM-produced CP-Ti exhibited better wear resistance and attributed this behaviour to its microstructure having α′ phase and finer grains. Toh et al (2016) investigated the dry sliding wear behaviour of Ti6Al4V alloy produced by electron beam melting (EBM), that is a similar technique to SLM, by testing against a 6 mm diameter of 100Cr6 steel ball under 1 N normal load, 2 cm/s sliding speed during 50000 cycles, where as-cast Ti6Al4V alloy was used as a control group. Although similar wear characteristics were observed on the samples produced by two different techniques, EBM-produced samples presented higher wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Even though, the authors reported that SLM-produced CP-Ti exhibited better wear resistance and attributed this behaviour to its microstructure having α′ phase and finer grains. Toh et al (2016) investigated the dry sliding wear behaviour of Ti6Al4V alloy produced by electron beam melting (EBM), that is a similar technique to SLM, by testing against a 6 mm diameter of 100Cr6 steel ball under 1 N normal load, 2 cm/s sliding speed during 50000 cycles, where as-cast Ti6Al4V alloy was used as a control group. Although similar wear characteristics were observed on the samples produced by two different techniques, EBM-produced samples presented higher wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…During this period, the dominated wear mechanism was severe adhesive wear and abrasive wear. Analogous wear behavior was studied in EBM Ti-6Al-4V parts by Toh et al [ 36 ]. When wear time reached at 6~15 min, these small debris were welded on worn surface too.…”
Section: Resultsmentioning
confidence: 99%
“…This is accompanied by a coarsening of the lamellar α phase. With an increase in bulk energy density, α lamellae can grow coarser [39][40][41].…”
Section: Direct Energy Deposition By Laser Wire (Lw)mentioning
confidence: 99%